Patient satisfaction: Public vs. private hospital in Central Sulawesi, Indonesia - Diah Mutiarasari; Indah Puspasari Kiay Demak; Elli Yane Bangkele; Rosmala Nur; Tri Setyawati (Elsevier, 2021)
Objective: The aim of the study was to compare the level of service satisfaction in public hospitals and private hospitals in Central Sulawesi. Methods: This was an analytical observational study with a cross-sectional approach. This research was conducted in 10 hospitals in Central Sulawesi. There were 1070 samples, which were 107 patients in each hospital. The level of patient satisfaction was measured using the Community Satisfaction Index (CSI) Questionnaire, which comprises of 38 closed questions. Results: The average overall satisfaction level was 75.99 (±11.28), which fell into category B for service quality and "Good" for service performance. The highest level of satisfaction was in competencies, reaching 78.25 (±13.48) and the lowest was in Handling Complaints, Suggestions and Feedback, reaching 73.90 (±14.01). In all categories, the level of satisfaction fell into category B for service quality and "Good" for service performance. Conclusions: The level of satisfaction of patients who sought treatment at private hospitals was higher than at public hospitals for all categories.